2014
DOI: 10.1016/j.crohns.2014.06.002
|View full text |Cite
|
Sign up to set email alerts
|

The intra-individual variability of faecal calprotectin: A prospective study in patients with active ulcerative colitis

Abstract: The present data reveal a great variability in the concentrations of calprotectin in stool samples collected during a single day. Since the levels of calprotectin increased with longer time between the bowel movements, it seems most appropriate to analyse stool from the first bowel movement in the morning. Moreover, storage of stool samples at room temperature for more than 3 days is not advisable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
147
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(164 citation statements)
references
References 25 publications
4
147
1
2
Order By: Relevance
“…Some efforts have now to be made to ensure commutability of results. Moreover, two recent studies have evidenced a high intra-individual variability, up to 40%, suggesting that a single determination of calprotectin may be insufficient to monitor relapse risk or treatment [36,70]. This high variability may be partly due to the variability of the extraction process since the relative quantity of water in stools may vary across the day.…”
Section: One or Several Thresholds: That Is The Questionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some efforts have now to be made to ensure commutability of results. Moreover, two recent studies have evidenced a high intra-individual variability, up to 40%, suggesting that a single determination of calprotectin may be insufficient to monitor relapse risk or treatment [36,70]. This high variability may be partly due to the variability of the extraction process since the relative quantity of water in stools may vary across the day.…”
Section: One or Several Thresholds: That Is The Questionmentioning
confidence: 99%
“…The collection of the stool samples could be done at home and then sent to the laboratory. However, one study has shown that the concentration of fecal calprotectin decreases from the third day after collection at room temperature [36]. Before assay, samples could be stored at 2-8 °C for 6 days.…”
Section: Technical Principle and Analytical Performances Pre-analyticsmentioning
confidence: 99%
“…FC levels decrease with increasing time between bowel movements; therefore, it is recommended that samples be obtained from the first bowel movement of the day (14). Because of the day-to-day variability in FC levels (14), retrieving samples at similar times over two consecutive days is preferable.…”
Section: Abstract: Disease Activity; Fecal Calprotectin; Inflammatormentioning
confidence: 99%
“…Furthermore, there has been some emerging evidence that FC levels may display intra-individual variability from day to day, or even within the same day, observed in individuals with active IBD [32], [33], quiescent IBD [34] and also normal individuals [35].…”
Section: Faecal Calprotectinmentioning
confidence: 99%
“…Therefore it is suggested that more attention needs to be paid to timing of sample collection and the practicalities of sample storage [32], and also that multiple or serial FC measurements [33] are obtained. Optimal cut-offs may also differ by disease (UC, CD), brand of assay used, distribution of inflammation, and age of patient [36].…”
Section: Faecal Calprotectinmentioning
confidence: 99%